2017
DOI: 10.1177/1178633617726781
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of CD14 Promoter Gene Polymorphism (rs2569190) is Associated With Regulation of Malaria Parasitemia and Susceptibility to Plasmodium falciparum Infection

Abstract: CD14 is a multifunctional receptor expressed on many cell types and has been shown to mediate immune response resulting in the activation of an inflammatory cascade, with polymorphism of its promoter (rs2569190) found to be associated with susceptibility to several diseases. In malaria infection, the CD14 gene demonstrated a pathogenic profile in regulating experimental cerebral malaria, with reports of elevated levels of soluble CD14 in serum of patients but no definitive conclusion. We present a detailed ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…On the other hand, the extensive genetic diversity and complexity of P. falciparum is also considered a major obstacle in the acquisition of natural immunity and vaccine development efforts. The findings in this study are consistent with previous reports that showed that these genes are highly polymorphic among the parasite population in southwestern Nigeria [ 12 , 31 , 32 ]. The genetic diversity analysis in the present study showed that P. falciparum populations in Idi Ayunre (rural) and Eleta (urban) exhibited an overall similar level of high genetic diversity, with MOI of 2.8 and 2.6, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, the extensive genetic diversity and complexity of P. falciparum is also considered a major obstacle in the acquisition of natural immunity and vaccine development efforts. The findings in this study are consistent with previous reports that showed that these genes are highly polymorphic among the parasite population in southwestern Nigeria [ 12 , 31 , 32 ]. The genetic diversity analysis in the present study showed that P. falciparum populations in Idi Ayunre (rural) and Eleta (urban) exhibited an overall similar level of high genetic diversity, with MOI of 2.8 and 2.6, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…CD14 gene is a major part of the innate immune system, and one of essential receptors needed to initiate an adequate response to infection [13][14][15]. Encounter with antigens trigger innate immune responses mediated by host genetic variations alongside additional benefits arising from prior exposure to such stimuli that may direct tolerance or susceptibility [18,35]. In this study, we dissected the genetic variation within the core promoter region of bovine CD14 gene to elucidate a deeper understanding of trypanosomosis tolerance in cattle.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have localized bovine health-related quantitative trait loci (QTL) to the genomic region of the CD14 loci [13,15]. In addition, results from malaria studies have shown CD14 promoter polymorphism to mediate an adaptive protective mechanism against severe disease [16,17], including regulation of parasitemia [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in human, mouse, cattle and sheep have shown that CD14 is significantly involved in innate immunity, playing major roles in susceptibility to tuberculosis, trypanosomosis, malaria and other bacterial infections (Sugawara et al, 2003;Ibeagha-Awemu et al, 2008;Xue et al, 2012;Ojurongbe et al, 2017). Other published reports have shown that there is a higher susceptibility to Mycobacterium tuberculosis infection in CD14 transgenic mice compared to the wild type (Reiling et al, 2002;Weiland et al, 2008).…”
Section: Introductionmentioning
confidence: 99%